Understanding the translation of second person address form in the specific context - Mansor, Nor Shahila (Publicacions URV, 2018)
Malay and English provide an interesting contrast with respect to nonvocative address systems. English no longer makes a distinction between formal and informal address pronouns, and avoids direct nominal address. In contrast, second person address in Malay is more complicated and involves pronominal and nominal forms. As a result, address forms in Malay can be confusing for nonnative speakers, as there are multiple potential equivalents for English’s ‘you’ but also because address forms in spoken Malay are often ellipse leaving only a bare verb. It is in this context that this study examines the translation of the English ‘you’ to Malay subtitles in Season One’s first episode of the famous America medical drama series, Grey’s Anatomy. The results show that the second person address expressed through ‘you’ in English appears in different ways in the Malay subtitle comprising of the Malay 2nd person pronoun, social title (T), social title with name (TN), kinship term (KT) and other expressions. In the first episode, 130 interactions were identified and 95% (209 instances) of the address forms were dominated by an explicit 2nd person pronoun while the remaining falls within other possibilities (e.g. substitution, deletion). This finding has implications on the understanding of the effect of translation from English to Malay on the use of address forms within this specific context.